Influence of Tympanosclerosis on Graft Uptake and Hearing Status in Patients Undergoing Underlay Myringoplasty - Prasad, PL; Bhattarai, H (Journal of Nepal Health Research Council, 2010)
Background: To assess the influence of tympanosclerosis on graft uptake and hearing status in patients undergoing underlay myringoplasty. Methods: Patients ≥12 years of age with the diagnosis of chronic suppurative otitis media tubo-tympanic type were included in this study. All patients participated in the study had undergone pre and postoperative pure tone audiometric evaluation and were divided into two groups, a study and a control, depending on the presence or absence of tympanosclerotic plaques. All patients underwent underlay myringoplasty and follow up was done after 10 weeks to note graft uptake and postoperative hearing evaluation. Results: Graft uptake was noted to be 96.1% in study group and 94.9% in control group. Similarly, graft uptake was noted in 96.36% where tympanosclerotic plaques were completely removed and in 95.23% where tympanosclerotic plaques were either partially removed or left as such. Post 0perative average hearing gain in study and control group was 12.1dB and 15.9dB respectively. While comparing postoperative hearing gain in cases where tympanosclerotic plaques were completely removed to those in whom tympanosclerotic plaques were either completely removed or left as such, it was 12.31dB in former and 13.67dB in later group, which was statistically non significant with P value of 0.83. Conclusions: Tympanosclerotic plaques, if removed as far as practicable, has no effect on either graft uptake and post operative hearing results in patient under going underlay myringoplasty. Key words: chronic suppurative otitis media tubo tympani type; puretone; audiogram; tympanosclerosis. DOI: 10.3126/jnhrc.v7i2.3019 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 116-119